2017
DOI: 10.1002/ajpa.23190
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination associated with higher diastolic blood pressure in a sample of American Indian adults

Abstract: Objectives Hypertension prevalence is high among American Indians (AIs). AIs experience a substantial burden of interpersonal racial discrimination, which in other populations has been associated with higher blood pressure. The purpose of this study is to understand whether racial discrimination experiences are associated with higher blood pressure in AIs. Materials and Methods We used the Everyday Discrimination Scale to evaluate the relationship between discrimination and measured blood pressure among 77 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…Cross-sectional studies ( n = 35) assessed race discrimination using a variety of self-report questionnaires and BP was measured with a range of methods (S2 Table). Of these cross-sectional studies, 22 [2437,3742] found significant associations between racial discrimination and BP in their primary analysis. Two cross-sectional studies [43,44] did not find a significant association between racial discrimination and BP in their primary analysis among the entire sample.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional studies ( n = 35) assessed race discrimination using a variety of self-report questionnaires and BP was measured with a range of methods (S2 Table). Of these cross-sectional studies, 22 [2437,3742] found significant associations between racial discrimination and BP in their primary analysis. Two cross-sectional studies [43,44] did not find a significant association between racial discrimination and BP in their primary analysis among the entire sample.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to discrimination and microaggressions are most commonly assessed in research via self-report measures and with African American samples [ 1 ], with relatively few measures that consider the unique racial/ethnic group experiences for AI/ANs (e.g., being told “you don’t look Indian”). Although some recent studies describe racial discrimination measures among AI/ANs (e.g., [ 17 , 49 , 55 ]), there has been limited replication or psychometric evaluation (see [ 17 ], for an exception).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the measures were designed for use with any racial/ethnic group (Everyday Discrimination Scale [ 63 ]; Experiences of Discrimination [ 32 ];) and one measure is an AI/AN-specific discrimination and microaggressions scale (Microaggressions Distress Scale, [ 57 ]). While the Everyday Discrimination Scale is the most common measure of discrimination across racial and ethnic groups, only four studies with Indigenous samples have been conducted [ 17 , 49 , 50 , 55 ], sometimes with varying items or instructions.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research implicates the repeated daily experiences of discrimination as both acute and chronic stressors, which increase allostatic load and have long-term health consequences [ 183 ]. Among IP around the world, discrimination and microaggressions have been associated with a higher likelihood of self-reported diabetes among southwest AIs [ 56 ], increased diabetes distress and higher blood pressure in AI from the northern Midwest [ 184 , 185 , 186 ], higher self-reported CVD (including heart attack and stroke) among Maori in New Zealand [ 187 ] and CVD diagnosis among the Indigenous Sami population in Norway [ 188 ].…”
Section: Adulthood Stress and Trauma And Cmdmentioning
confidence: 99%